TNF stimulation primarily modulates transcriptional burst size of NF‐κB‐regulated genes - Victor L Bass; Victor C Wong; M Elise Bullock; Suzanne Gaudet; Kathryn Miller‐Jensen (Molecular Systems Biology)
Abstract Cell‐to‐cell heterogeneity is a feature of the tumor necrosis factor (TNF)‐stimulated inflammatory response mediated by the transcription factor NF‐κB, motivating an exploration of the underlying sources of this noise. Here, we combined single‐transcript measurements with computational models to study transcriptional noise at six NF‐κB‐regulated inflammatory genes. In the basal state, NF‐κB‐target genes displayed an inverse correlation between mean and noise characteristic of transcriptional bursting. By analyzing transcript distributions with a bursting model, we found that TNF primarily activated transcription by increasing burst size while maintaining burst frequency for gene promoters with relatively high basal histone 3 acetylation (AcH3) that marks open chromatin environments. For promoters with lower basal AcH3 or when AcH3 was decreased with a small molecule drug, the contribution of burst frequency to TNF activation increased. Finally, we used a mathematical model to show that TNF positive feedback amplified gene expression noise resulting from burst size–mediated transcription, leading to a subset of cells with high TNF protein expression. Our results reveal potential sources of noise underlying intercellular heterogeneity in the TNF‐mediated inflammatory response.